Fog and overcast low-level stratiform cloud characteristics at the airport of Lviv from surface observations - Густенко О.С.; Хоменко І.А. (Київський національний університет імені Тараса Шевченка, 2024)
Fog and low-level stratiform clouds have been identified as hazardous weather phenomena, resulting in various losses, including time, money, and, most importantly, human lives in aviation transportation. Fog and low-level stratus pose substantial risks to aviation, especially during takeoff, landing, and low-level flying, due to conditions of reduced visibility. Forecasting low-level stratiform clouds and fog is a challenging aspect of aviation meteorology due to the similarity in the mechanisms of their formation, complex and non-deterministic processes in the atmospheric boundary layer, and their high dependence on local conditions. Given these challenges, weather observations, a primary source of information on local meteorological conditions, can be utilized to establish statistical dependencies of fog/low-level stratus characteristics, enabling the differentiation of both phenomena and the improvement of their forecast accuracy. To find the characteristics of fog and low-level stratiform clouds and identify local dependencies for enhancing the forecast of these phenomena at Lviv Airport, Ukraine, three-hourly METARs information from the airport’s Meteorological Station for the period 2010-2020 were analyzed. Employing a statistical approach, the annual, seasonal, and diurnal distribution of fog and low-level stratiform clouds, along with their frequency distribution associated with various meteorological parameters, were determined. Applying a statistical approach, the empirical relationship between the occurrence of fog/overcast low-level stratus and a set of potential local predictors, namely 2 m air temperature and relative humidity, was identified. The results obtained can be instrumental in providing historical data to weather forecast models and improving the accuracy of forecasts for fogs and low-level stratus.

Тумани та низька суцільна хмарність є небезпечними погодними явищами, які дуже часто призводять до втрати часу, грошей і навіть людських життів під час авіаційних перевезень. Вони становлять значну небезпеку для авіації, особливо під час зльоту та посадки літаків, а також при польоті повітряних суден на низьких висотах через суттєве обмеження видимості. Прогноз низької суцільної хмарності і туманів є одним із найскладніших питань авіаційної метеорології через схожість механізмів утворення цих явищ, складність і недетермінованість процесів в межовому шарі атмосфери, а також сильну залежність появи туманів і низької хмарності від місцевих умов. Через наведені обставини дані аеродромних спостережень, які саме і є одним з основних джерел інформації щодо локальних метеорологічних умов, є необхідною основою для встановлення локальних статистичних залежностей, які дозволять розмежувати обидва явища і прогнозувати їхні характеристики. Для отримання режимних характеристик низької суцільної хмарності і туманів та встановлення локальних залежностей, які дозволили б удосконалити методи прогнозу туманів і низької суцільної хмарності в аеропорту «Львів», використано дані тригодинних наземних метеорологічних спостережень в коді METAR за період 2010-2020 рр. На основі створеної бази даних METAR отримано річний, сезонний і добовий розподіл туманів і низької суцільної хмарності, а також розподіл повторюваностей різних метеорологічних величин при туманах і суцільній низькій хмарності. Застосовуючи статистичний підхід, виявлено емпіричні залежності наявності туману/суцільної низької хмарності від комплексу потенціальних локальних предикторів – відносної вологості і температури повітря на рівні двох метрів. Отримані результати можуть бути використані для забезпечення моделей прогнозу погоди архівними даними та удосконалення статистичних прогнозів туманів і суцільної низької хмарності.
Режимні характеристики туманів і суцільної низької хмарності в аеропорту «Львів» за даними наземних спостережень
Keywords: Cуцільна низька хмарність; туман; дані наземних спостережень; METAR; Львів; Overcast low-level stratiform clouds; fog; surface observational weather data; METAR; Lviv